Effect of Chloroform Extraction Site of Jiangu Granule on Obteoblast Differentiation in Vitro via BMP2/Smad1/Runx2/Osterix Signaling Pathway - ZHOU Fen; SUN Yuqing; SUN Pan; ZHANG Chutian; YANG Juan; LIN Yanping (康复学报)
ObjectiveTo investigate whether the chloroform extraction site of Jiangu Granule could affect the differentiation of osteoblast in vitro via BMP2/Smad1/Runx2/Osterix signaling pathway.MethodsPrimary osteoblasts were extracted from the calvaria of BALB/c mice born less than 3 days old, and the extracted cells were identified by alkaline phosphatase staining; the third-generation osteoblasts in good growth condition were selected as experimental subjects. The chloroform extraction site of Jiangu Granule was diluted to different concentration gradients, which included 7 drug concentration groups of 0, 2, 4, 8, 16, 32, and 64 ng/mL set for cell intervention. MTT method was used to screen the optimal concentration of the chloroform extraction site of Jiangu Granule to promote the proliferation of osteoblasts, which was used as the optimal drug intervention concentration for follow-up experiments. The third-generation cells were extracted and divided into 4 groups, namely blank group, inhibitor group (intervened by BMP2 inhibitor Noggin), drug group (intervened by Jiangu Granule chloroform extraction site) and inhibitor plus drug group (intervened by Noggin plus Jiangu Granule chloroform extraction site). After cell interventions in each experiment group, RT-PCR was used to detect the mRNA expression levels of BMP2, Smad1, Runx2, Osterix and osteoblast differentiation-related genes ALP and Collagen Ⅰ in each group. Western blot was used to detect the protein expressions of BMP2, Smad1, Runx2, Osterix, ALP and Collagen Ⅰ in each group, and the effect of chloroform extraction site of Jiangu Granule on osteoblast differentiation was observed.ResultsThe alkaline phosphatase staining showed the positive rate of osteoblasts in the collected primary cells was as high as 90%. The results of MTT method showed that when the concentration of chloroform extracted from Jiangu Granule was 32 ng/mL, the osteoblasts showed the fastest proliferation, and reached the peak of proliferation after 2 days of intervention. Therefore, 32 ng/mL concentration gradient of Jiangu Granule was selected as the plan for 2 days intervention. The optimal intervention concentration of the chloroform extraction site was used for follow-up experiments. RT-PCR and Western blot detection showed that, compared with the blank group, the expression levels of each index gene in the inhibitor group significantly decreased, and the relative protein expression significantly decreased (P<0.01 or P<0.05); compared with the blank group, the expression levels of 6 index genes in the drug group significantly increased, and the relative protein expression also significantly increased (P<0.01 or P<0.05); compared with the inhibitor group, the expression levels of index genes and proteins in inhibitor plus drug group significantly increased (P<0.01 or P<0.05).Conclusion1) The gene and protein expressions of Smad1, Runx2, and Osterix significantly decreased when Noggin was used to inhibit the expression of intracellular BMP2. At the same time, osteoblast differentiation-related indicators ALP and Collagen Ⅰ also significantly decreased, suggesting that the BMP2 pathway could be closely related to osteoblast differentiation. 2) After the chloroform extraction site of Jiangu Granule intervention in osteoblasts, the expression of BMP2, Smad1, Runx2, Osterix and osteoblast differentiation-related indexes ALP and Collagen Ⅰ genes and proteins increased in the cells, which promoted the differentiation of osteoblast-like cells. It suggested that the chloroform extraction site of Jiangu Granules could promote the differentiation of osteoblasts by regulating the BMP2/Smad1/Runx2/Osterix pathway, so as to prevent and treat postmenopausal osteoporosis.